SIFAT ORANG YANG DIBERI HIDAYAH (PETUNJUK) OLEH ALLAH SWT - Achsanudtaqwin, Achris (TARBAWI:Journal on Islamic Education, 2023)
Hidayah is a guidance from Allah SWT which is very crucial for human life. Without guidance, people tend to get lost in their journey. Many people reject Allah's guidance and choose the wrong path, even though they claim to be Muslims. Therefore, it is important to understand the nature of people who are guided by Allah. This research applies a library research method with a descriptive approach, where data is collected from various books, reports, and relevant references. The results show that people who are guided by Allah SWT have traits such as obedience to Allah, awareness of the truth, gratitude, tawakal, love for the Prophet Muhammad, and the desire to do good. They also have a forgiving, compassionate nature, as well as being consistent in prayer and accepting Allah's destiny with sincerity.